Mucosal healing and mortality in coeliac disease. Issue 3 (28th November 2012) - Lebwohl, B.; Granath, F.; Ekbom, A.; Montgomery, S. M.; Murray, J. A.; Rubio‐Tapia, A.; Green, P. H. R.; Ludvigsson, J. F.
Summary Background Coeliac disease (CD), characterised by the presence of villous atrophy (VA) in the small intestine, is associated with increased mortality, but it is unknown if mortality is influenced by mucosal recovery. Aims To determine whether persistent VA is associated with mortality in CD. Methods Through biopsy reports from all pathology departments (n = 28) in Sweden, we identified 7648 individuals with CD (defined as VA) who had undergone a follow‐up biopsy within 5 years following diagnosis. We used Cox regression to examine mortality according to follow‐up biopsy. Results The mean age of CD diagnosis was 28.4; 63% were female; and the median follow‐up after diagnosis was 11.5 years. The overall mortality rate of patients who underwent follow‐up biopsy was lower than that of those who did not undergo follow‐up biopsy (Hazard Ratio 0.88, 95% CI: 0.80–0.96). Of the 7648 patients who underwent follow‐up biopsy, persistent VA was present in 3317 (43%). There were 606 (8%) deaths. Patients with persistent VA were not at increased risk of death compared with those with mucosal healing (HR: 1.01; 95% CI: 0.86–1.19). Mortality was not increased in children with persistent VA (HR: 1.09 95% CI: 0.37–3.16) or adults (HR 1.00 95% CI: 0.85–1.18), including adults older than age 50 years (HR: 0.96 95% CI: 0.80–1.14). Conclusions Persistent villous atrophy is not associated with increased mortality in coeliac disease. While a follow‐up biopsy will allow detection of refractory disease in symptomatic patients, in the select population of patients who undergo repeat biopsy, persistent villous atrophy is not useful in predicting future mortality.